Islamophobia and anti-antisemitism: the case of Hungary and the 'Soros plot' - Kalmar, Ivan (Patterns of prejudice, 2020)
The more than a million, mostly Muslim, arrivals in the European Union in recent years have given mainstream politicians an opportunity to generate and exploit the public racist, xenophobic and ultra-nationalist urges of the sort that had previously been the exclusive preserve of the extreme right. This successful vote-getting strategy hingeS on disassociating ethno-religious hatred, which Islamophobia is, from its most stigmatized example in Europe: antisemitism. Nowhere has this process been clearer than in Hungary, infamous for 'solving' the migration crisis by erecting a wire fence along its borders. Viktor Orbán and his ruling Fidesz party have stolen the racist thunder of the far-right Jobbik party, but without the latter's once open antisemitism. Jobbik has responded by also seemingly renouncing antisemitism, ignoring the protests of its more die-hard neo-Nazi supporters. Kalmar's article focuses on the government's use of a conspiracy theory about the Jewish financier George Soros as an example of exploiting antisemitism while claiming to oppose it. It suggests that the process of rejecting antisemitism, if disingenuously, in order to legitimize Islamophobic racism in Hungary is a useful model for examining similar processes in much of the Euro-Atlantic world.